EUROPE OUT OF FOCUS: MEDIA REPORTING ON EU INTEGRATIONS IN ONLINE MEDIA IN BOSNIA-HERZEGOVINA - Turčilo, Lejla; Belma, Buljubašić (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This article analyses ways in which media in Bosnia-Herzegovina report on EU integrations, as one of key processes that are happening in B&H at the moment. Country makes quite slow progress towards the EU and media, as a consequence of that, do not show huge interest for reporting about integration porcess, mainly reporting superficially, in a burraucratic manner and withour deeper analysis. This does not enable citizens to better understand benefits from the EU integrations and does not increase interest nor support of citizens to integrations. Based on the results of this research, authors conclude that public interest and orientation function of media are not key in media reporting on EU i Bosnia-Herzegovina.